The Trinity of Transmission Issues: Siting, Access and Pricing - Brown, Ashley (Maine Policy Review, 1993)
Ashley Brown is not only a commissioner of the Public Utilities Commission of Ohio, he is also one of the most widely-respected authorities in the U.S. today on the regulation of electric utilities. He is particularly known for his vocal efforts to forge a more cooperative state-federal relationship in electrical regulation. This article is an edited excerpt from his keynote address at the PURE ’93 Conference.